2015
DOI: 10.1103/physreva.92.053404
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon double ionization of atomic beryllium with ultrashort laser pulses

Abstract: We investigate the two-photon double ionization of beryllium atom induced by ultrashort pulses. We use a time-dependent formalism to evaluate the ionization amplitudes and generalized cross sections for the ejection of the 2s 2 valence shell electrons in the presence of a fully occupied 1s 2 frozen core shell. The relative contributions of the two-photon direct and sequential process are systematically explored by varying both pulse duration and central frequency. The energy and angular differential ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the Seq(A) process, the two valence electrons are ejected with close kinetic energies (E int < 1 eV) and are hence highly correlated. In contrast with the Seq(A) process via Be + (2p), the sequential ionization process Seq(B) that proceeds via the Be + (2s) (allowed only forhω > 18.2 eV) releases electrons that have distinct kinetic energies and are thus lowly correlated in energy sharing [5,12]. In the direct two-electron ejection process, the two photons of 15 eV each are absorbed almost simultaneously by the electron pair.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Seq(A) process, the two valence electrons are ejected with close kinetic energies (E int < 1 eV) and are hence highly correlated. In contrast with the Seq(A) process via Be + (2p), the sequential ionization process Seq(B) that proceeds via the Be + (2s) (allowed only forhω > 18.2 eV) releases electrons that have distinct kinetic energies and are thus lowly correlated in energy sharing [5,12]. In the direct two-electron ejection process, the two photons of 15 eV each are absorbed almost simultaneously by the electron pair.…”
Section: Resultsmentioning
confidence: 99%
“…The frozen core approximation is valid only if the atom is submitted to photons that have just enough energy to eject the valence electrons, but not enough to reach the core avoiding hence the photoionization of the inner electrons. Few theoretical studies of the double ionization process by two-photon absorption in Be have been reported [5,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods utilized in this work for treating photoionization of two electrons from a target with additional electrons has been previously described in greater detail in the both a time-independent framework, [8,9] and with a time-dependent treatment involving ultrashort laser pulses [11,21]. Thus, here we provide a brief overview of the most important points in applying the method to magnesium.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The formalism we employ to study this process requires denoting the neon-like core occupancy of all but the valence electrons, which provide a closed-shell Coulomb and exchange interaction with the outer 3s 2 electrons that feel the action of the photon towards the double continuum. The construction of atomic orbitals out of an underlying radial grid to represent these core electrons facilitates the approximation of holding them fixed in a configuration-interaction expansion and has been applied to atomic beryllium in both a time-independent formalism for one-photon double ionization [8,9,13], and in a time-dependent framework [11,21] for consideration of two-photon processes that remove the outer electrons. This method has also been applied to examine the double photoionization process for neon [22], which unlike the systems considered here, leaves behind an open-shell target with distinct final state couplings for the residual dication.…”
Section: Introductionmentioning
confidence: 99%